A Comparative Voltammetric Study of a Chemically Modified Octa(3-Aminopropyl)Octasilsesquioxane and DAB-AM-16 Dendrimer Supported on the Silica Gel Surface for Dipyrone Detection - do Carmo, Devaney Ribeiro [UNESP] (2020)
Octa(3-aminopropyl)octasilsesquioxane and DAB-AM-16 dendrimer, due to their specific chemical and physical properties, give wide application in various fields of science. Because they have a large number of NH2 reactive groups at their ends, they are capable of interacting with different substances, generating in this way different compounds with enormous analytical potential that can be used in the electrocatalytic determinations and oxidations of some substances of environmental and biological interest. In this work, after a rigorous voltammetric study, the electroanalytical potentiality of the chemically Ni2+ metal ions chealed silica gel surface modified with octa(3-aminopropyl)octasilsesquioxane and DAB-AM-16 dendrimer was tested for dipyrone detection. The cyclic voltammogram of the graphite paste electrode, with both materials (20% w/w) showed two redox process. The following formal potential (Eθ′) values for both materials were identical: (Eθ′)I = 0,26 V; (Eθ′)II = 0,51 V vs Ag/AgCl (KCl = 1.0 mol L−1; v = 20 mV s−1). For dipyrone detection assay, the limite of detection were of 9.17 × 10−5 mol L−1 with an amperometric sensitivity of 15.78 mA / mol L−1 with a relative standard deviation of ±3% (n = 3) and of 4.79 × 10−4 mol L−1 with an amperometric sensitivity of 11.10 mA / mol L−1 with a relative standard deviation of ±2% (n = 3) respectively for silica gel surface modified with octa(3-aminopropyl)octasilsesquioxane and DAB-AM-16 dendrimer.